Pengembangan Penilaian Autentik Pembelajaran Teks Dialog Bahasa Jawa Kelas VII - Meliana, Siti; Sudi Utami, Esti; Sukoyo, Joko (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
Assessment is once of process study which is conducted to measure students by basic competency. Lack of reference to teachers for assessment dialog text make obstacles for giving assessment to students. This limitation made basic must be need assessment of development technique where can helping teachers to give an assessment. This research has a purpose to develop learning instrument assessment dialog of text Javanese Language. This research has used research and development methods, with five-stage of research, include identity potency and problem, data collection, design product, validation design, and then revision of the design. Collection data used by interviews andquestionnaires instruments. Result of this research in the form of authentic assessment learning dialog text Javanese Language. The assessment of instruments is a question of multiple-choice, task, work method/practice, and product. Result of validation has to show acquisition average score at the question of multiple choice 11,72 (enough) from evaluation expert and score 12,11 (good) from teacher expert, and while the average score assessment of tasking, work method/practice, and product 3,7 (good) from expert and 3,1 (enough) 2 from teachers. Repaired has done on the selection of diction, sentence structure, and repair choice answers.